2011
DOI: 10.1177/1078390310392374
|View full text |Cite
|
Sign up to set email alerts
|

Program Planning and Staff Competencies for Forensic Assertive Community Treatment: ACT-Eligible Versus FACT-Eligible Consumers

Abstract: Purpose Forensic assertive community treatment (FACT) is a recent adaptation of the assertive community treatment (ACT) model; however, more information is needed about how FACT and ACT consumers differ and how FACT should be modified to accommodate these differences. Methods Linked, multisystem administrative data from King County, Washington were used to compare the demographic, clinical and criminal justice characteristics of ACT- and FACT-eligible consumers. Results FACT consumers were more likely to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Staffing was examined with an emphasis on identifying team members not routinely found within standard ACT teams, such as forensic peer specialists, mental health court liaisons, or probation officers. Special training, requisite experience, or other competencies were also recorded, as research suggests that FACT patients have special needs compared to ACT patients 32 . Admission criteria were likewise noted, with an emphasis on identifying both mental health and criminal justice criteria.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Staffing was examined with an emphasis on identifying team members not routinely found within standard ACT teams, such as forensic peer specialists, mental health court liaisons, or probation officers. Special training, requisite experience, or other competencies were also recorded, as research suggests that FACT patients have special needs compared to ACT patients 32 . Admission criteria were likewise noted, with an emphasis on identifying both mental health and criminal justice criteria.…”
Section: Methodsmentioning
confidence: 99%
“…74,75 To help overcome cultural and language barriers to their engagement, the racial/ethnic demography of FACT service providers should approximate that of their service recipients. 32 Although ACT is an essential element of FACT, research has consistently suggested that ACT alone has little or no effect at preventing arrest and incarceration among ACT service recipients. 30,31,76 Still, some mental health professionals have continued to suggest that ACT is sufficient to prevent criminal recidivism among justice-involved patients.…”
Section: Essential Elements Of Factmentioning
confidence: 99%
See 2 more Smart Citations
“…Clients of ForFACT services are distinctly different from clients of non-ForFACT teams. ForFACT clients were, for example, more likely to have experienced homelessness (Cuddeback & Morrisey, 2011). ForFACT clients were also shown to have higher rates of psychotic disorders and more antisocial personality disorders, whereas non-ForFACT clients showed higher rates of affective disorders, panic disorder, and posttraumatic stress disorder (Cuddeback & Morrisey, 2011).…”
mentioning
confidence: 99%